Feeding ecology, residency patterns and migration dynamics of bull sharks (Carcharhinus leucas) in the southwest Indian Ocean - Daly, Ryan (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Bull sharks (Carcharhinus leucas) are globally distributed top predators that play an important ecological role within coastal marine communities. However, little is known about how the spatial and temporal scales of their habitat use are associated with their ecological role. In this study, a population of sub-adult and adult bull sharks were investigated within a remote subtropical marine community in the southwest Indian Ocean off the coast of southern Mozambique. The main objectives of the study were to test a minimally invasive remote biopsy sampling method; to investigate the feeding ecology of bull sharks; and to investigate the temporal and spatial scales of bull shark residency patterns and migration dynamics. Biopsy tests on free-swimming bull sharks showed that the devised sampling technique provided a minimally invasive and consistent method (biopsy retention rate = 87%) to obtain muscle tissue samples sufficiently large enough (310Â±78mg, mean Â± SD) for stable isotope analysis. Results from the stable isotope analysis showed that adult bull sharks appeared to exhibit a shift towards consistentlyhigher trophic level prey from an expanded foraging range compared to sub-adults, possibly due to increased mobility linked with size. Additionally, bull sharks had significantly broader niche widths compared to top predatory teleost assemblages with a wide and enriched range of Î´13C values relative to the local marine community, suggesting that they forage over broad spatial scales along the east coast of southern Africa. Results from the passive acoustic telemetry investigation, conducted over a period between 10 and 22 months, supported these findings showing that the majority of tagged adult sharksexhibited temporally and spatially variable residency patterns interspersed with migration events. Ten individuals undertook coastal migrations that ranged between 433 and 709km (mean = 533km) with eight of these sharks returning to the study site. During migration, individuals exhibited rates of movement between 2 and 59km.d-1 (mean = 17.58km.d-1) and were recorded travelling annual distances of between 450 and 3760km (mean = 1163km). These findings suggest that adult bull sharks are not the sedentary species once thought to be but rather, consistently move over broad spatial scales on the east coast of southern Africa and play an important predatory role shaping and linking ecological processes within the southwest Indian Ocean.
Keywords: Bull shark -- Ecology; Bull shark -- Feeding and feeds